MAGNESIUM ALLOYS FOR BIODEGRADABLE IMPLANTS: INNOVATIONS, CHALLENGES, AND FUTURE DIRECTIONS IN BIOMEDICAL APPLICATIONS - Saxenaa, Ayush; Trivedi, Vaibhav; Goel, Ankur (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Magnesium (Mg)and its alloys are broadly utilized forbiomedical applications owing to their biocompatibility, mechanical properties, and potential to avoid the need for secondary surgeries. However, the rapid and non-uniform degradation of Mg alloys in physiological environments remains a challenge, hindering their clinical adoption. Present work examinesadvancements in the development, surface modification, and performance optimization of Mg-based alloys for biomedical applications. The work discusses the effect of synthesis methods and surface treatments on the characteristics of corrosion and mechanical behaviour and biocompatibility of Mg alloys. Additionally, the review highlights the ongoing challenges in controlling the degradation rate of Mg alloys and proposes future research directions aimed at achieving a balance between biodegradability and mechanical stability. These comprehensive analyses of the current state of Mg-based biomaterials offer insights into their potential for next-generation implant technologies and bring out the need for continued innovation to reduce the existing limitations.